Aktivitas Antidiabetika Ekstrak Etanol Herba Sambiloto (Andrographis paniculata Nees (Acanthaceae)) - Elin Yulinah; Sukrasno Sukrasno; Muna Anom Fitri (Institut Teknologi Bandung, 2001)
Antidiabetic activity of the ethanol extract of Andrographis paniculata Nees herbs had been tested using glucose tolerance test in rat and alloxan induced diabetic mice. The extract reduced rat blood glucose at the dose of 2.0 g/kg bw but there was no effect observed at dose of 0.50 g/kg bw and 1.0 g/kg bw. It is interesting that the extract at doses 2.1 g/kg bw and 2.8 g/kg bw, and the effect was much lower at 3.5 g/kg bw also showed the capacity to reduce blood glucose level of alloxane induced diabetic mice.